Live longer, work longer? An investigation of the health capacity to work at older ages in Denmark using combined register and survey data - Maiken Skovrider Aaskoven; Jørgen Lauridsen; Trine Kjær (Journal for Labour Market Research, 2024)
Publicly funded pension systems are facing the challenge of remaining financially sustainable without lowering pensions. Raising the statutory retirement age gradually in line with the increase in life expectancy has been a key measure to solve the problem. The implicit assumption is that the additional years of life are lived in good health, or as a minimum that health status is compatible with work. However, some individuals may not have the ability to work. Furthermore, a uniform retirement age ignores the different exposures to morbidity and mortality risks across social groups. Consequently, it is important to examine whether the health of older individuals will allow them to continue working and whether there is significant heterogeneity in the ability to work. Combining the Survey of Health, Ageing and Retirement in Europe (SHARE) with data from the Danish registers enables us to create a composite health index that includes an extensive range of health indicators. Utilising the health capacity to work approach, we estimate the health capacity to work among Danes aged 55 and above. We divide health capacity into physical and mental health. We investigate heterogeneity in health capacity across educational and occupational attainment. Substantial additional work capacity is found for older Danes. Depending on the type of health index applied, the health capacrk varies. There is evidence of a socio-economic gradient in work capacity. Results thereby show that policies that intend to utilise the additional work capacity should consider heterogeneity in health.
Keywords: E24; I14; J21; J14; J26; 330; Heterogeneity; Retirement; Health; Denmark; SHARE; Work capacity